Răspuns :
[(x+1)/2x-(x-1)/3x]6x/(x+5)=
{[3(x+1)-2(x-1)]/6x}·6x/(x+5)=
(3x+3-2x+2)/6x·6x/(x+5)=
(x+5)/(x+5)=1
{[3(x+1)-2(x-1)]/6x}·6x/(x+5)=
(3x+3-2x+2)/6x·6x/(x+5)=
(x+5)/(x+5)=1
[tex]\it E(x)= \left(\dfrac{x+1}{2x}-\dfrac{x-1}{3x}\right)\cdot\dfrac{6x}{x+5}[/tex]
Numitorul comun este 6x.
Se amplifică prima fracție cu 3, iar a doua , cu 2.
Obținem:
[tex]\it E(x) =\dfrac{3x+3-2x+2}{6x} \cdot \dfrac{6x}{x+5} = \dfrac{x+5}{6x}\cdot \dfrac{6x}{x+5} = 1[/tex]
Numitorul comun este 6x.
Se amplifică prima fracție cu 3, iar a doua , cu 2.
Obținem:
[tex]\it E(x) =\dfrac{3x+3-2x+2}{6x} \cdot \dfrac{6x}{x+5} = \dfrac{x+5}{6x}\cdot \dfrac{6x}{x+5} = 1[/tex]